Structure, thermodynamics and diffusion in asymmetric binary mixtures: a molecular dynamics simulation study. (3rd September 2018) - Padidela, Uday Kumar; Khanna, Tarun; Behera, Raghu Nath
ABSTRACT: Structural and thermodynamic properties as well as diffusion coefficients of binary fluid mixtures with asymmetry in mass, size, charge and their combinations have been studied using classical molecular dynamics simulations. The fluid mixture is modelled as spherical particles interacting via the Weeks–Chandler–Andersen and Coulomb potential. The diameter, charge and mass of the fluid particles are in the range 6–60 Å, 1–10 e and 1—500 amu, respectively. Systematic variations in pair-correlation functions, thermodynamic properties as well as the self-diffusion coefficient are found with the size, charge and mass ratio of the particles. The self-diffusion coefficient for systems having more than one type of asymmetry is calculated and expressed in terms of diffusion coefficients of systems with only one type of asymmetry.